Industrial pretreatment of lignocellulosic biomass: A review of the early and recent efforts to scale-up pretreatment systems and the current challenges - Saad, Marcelo B.W. [UNESP]; Gonçalves, Adilson R. [UNESP] (Elsevier, 2024)
Renewable alternatives to fossil fuels are now a worldwide effort, and biofuels can play an essential role in a sustainable energy matrix. The great potential of lignocellulosic biomass as feedstock for bioethanol production has been underexplored due to technological barriers and the costs involved. However, a new chapter in this history has been written recently after eight different biomass-to-ethanol processes achieved the industrial scale, leading bioethanol technologies to a new step of maturity due to challenges faced and lessons learned. The pretreatment of biomass has been recognized as the most complex step in the cellulosic ethanol production processes and the reason for the failure of some industrial initiatives. Pretreatment represents an essential process to prepare lignocellulosic material for subsequent hydrolysis and fermentation, and this review aims to describe the early and recent efforts to scale-up pretreatment systems and the current challenges of pretreatment operations. Since the early 2010s, a global running for cellulosic ethanol resulted in eight industrial facilities around the world; agricultural residues like corn stover, corn cob, wheat straw, sugarcane bagasse, and sugarcane straw were used by POET-DSM, Raízen, Beta Renewables, GranBio, Abengoa, DuPont, Clariant, and Longlive Bio-tech as feedstock for bioethanol production. Pretreatment technologies, including diluted acid, steam explosion, dilute ammonia, and mechanical refining, were then experienced industrially through batch or continuous systems performed in one or two conversion stages. The pretreatment systems employed by each cellulosic biorefinery are analyzed in this review, and the process conditions and strategies applied are discussed based on public information available. Furthermore, a historical background of the early developments of acid hydrolysis of cellulose and the transition to the modern pretreatment concept is provided. Typical batch reactors employed during the 1900s were replaced by continuous reactors aiming for high productivity. An overview of digesting systems used by the pulp and paper industry is explored, which were initially developed for pulping and recently adapted to perform biomass pretreatment. Special attention is paid to describing vertical and horizontal continuous digesters and mechanical disc refiners, the leading equipment used in industrial pretreatment systems. Additionally, current pretreatment challenges are discussed based on pilot and industrial experience. Biorefineries faced low throughput capacity due to unstable operation and high wear damage to equipment caused by mineral impurities. The impact of feedstock quality and preconditioning processes on pretreatment operation is also reviewed. Feedstock collection, storage, and cleaning have been considered critical operations for a successful pretreatment process; best practices from the non-wood pulping industry are analyzed, providing an important reference for biorefineries. Challenges related to pretreatment uptime, throughput, and yield are considered, and the control of residence time in horizontal continuous reactors is discussed. Finally, recent biorefinery experiences resulted in significant progress for industrial pretreatment's learning curve; this review contributes to consolidating the knowledge generated by these pioneer initiatives while this unique technology continues to evolve.
Keywords: Bioethanol; Biofuel; Biorefinery; Lignocellulosic biomass; Pretreatment